2018
DOI: 10.1039/c8ra00106e
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial modification of basalt fiber filling composites with graphene oxide and polydopamine for enhanced mechanical and tribological properties

Abstract: Due to the chemical inertness of the basalt fiber (BF) surface, the weaker interfacial bonding between BF and polymer matrices will seriously affect the further application of basalt fiber enhanced composites. In this study, a continuous and compact graphene oxide (GO) layer was grafted onto the surface of basalt fiber (BF) using biomimetic polydopamine (PDA) as a bridge to improve the mechanical and tribological properties of polyamide 6. The impact and flexural strength of the PA6 composites filled by the GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…The successful functionalization of GO NPs can be confirmed by the emerging bands in the spectra of GO-PDA that are attributed to the amide functionality at~1285, 1500, 1619, 3038, and 3184 cm −1 . These bands have been previously reported in literature and were related to PDA [40][41][42]. Further, it was found that the C=O band at 1707 cm −1 was almost disappeared with GO-PDA demonstrating a partial reduction of GO NPs [28].…”
Section: Structural Properties Of Go and Go-pdasupporting
confidence: 78%
“…The successful functionalization of GO NPs can be confirmed by the emerging bands in the spectra of GO-PDA that are attributed to the amide functionality at~1285, 1500, 1619, 3038, and 3184 cm −1 . These bands have been previously reported in literature and were related to PDA [40][41][42]. Further, it was found that the C=O band at 1707 cm −1 was almost disappeared with GO-PDA demonstrating a partial reduction of GO NPs [28].…”
Section: Structural Properties Of Go and Go-pdasupporting
confidence: 78%
“…The results showed that the adhesion rate, immobilization ratio, and biomass of modified BF were higher than that of BF. In Wang’s work [ 21 ], a continuous and compact graphene oxide (GO) layer was grafted onto the surface of BF using biomimetic polydopamine as a bridge to improve the mechanical and tribological properties of polyamide 6 (PA6). The impact and flexural strength of the PA6 composites indicated that the introduction of GO gave a large improvement in interface bonding performance between BF and PA6 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it is noteworthy that carbon materials can be engineered to exhibit specific catalytic capabilities for specific electrocatalytic reactions by varying the doping types, sites, and levels [21][22][23][27][28][29][30][31]. Although some of these have recently been developed as HER electrocatalysts [32][33][34], the employment of carbon-based nanomaterials as high-performance [38], (b) schematic showing the steps of the C-PDA film transfer onto Si wafer, (c) and the scheme of synthesis of N-doped carbon using dopamine as a precursor [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of the carbonized polydopamine (C-PDA) for hydrogen generation. (a) Schematic of self-polymerization of dopamine on target substrate using the dipping method[38], (b) schematic showing the steps of the C-PDA film transfer onto Si wafer, (c) and the scheme of synthesis of N-doped carbon using dopamine as a precursor[50][51][52].…”
mentioning
confidence: 99%